Patients' Evaluation of the Quality of Diabetes Care (PEQD): development and validation of a new instrument. Issue 2 (1st June 2002) - Pouwer, F; Snoek, F J
Abstract : Objectives: To develop a brief measure of patients' evaluation of the quality of diabetes care and to study predictors of consumers' rating of the quality of diabetes care. Design: A prospective design. Subjects: 176 adults with type 1 (39%) or type 2 (61%) diabetes. Main measures: Demographic variables, HbA1c, number of diabetes complications, satisfaction with diabetes care, diabetes related distress, and fear of hypoglycaemia were assessed by self-report. In addition, satisfaction with diabetes care and evaluations about quality of the care were measured at 16 month follow up. Statistical analysis comprised principal component analyses, Cronbach's alpha, t tests, Pearson's correlation, and linear regression analyses. Results: Results in the literature were used to develop the 14 items of the Patients' Evaluation of the Quality of Diabetes Care (PEQD) scale, assessing the most important aspects of the quality of diabetes care as delivered by the specialist in internal medicine (internist) and the diabetes nurse specialist (DNS). Two principal components analyses (internist/DNS) both yielded one 14 item factor with a high internal consistency. Satisfaction with diabetes care, fewer diabetes related complications, fewer treatment related problems, and a low level of worries about hypoglycaemia were predictors of a more positive evaluation of diabetes care delivered by the internist. Sociodemographic variables were not related to the patients' evaluations of the quality of diabetes care. Conclusions: The PEQD comprises different aspects of quality of diabetes care and can be regarded as a suitable instrument for evaluating patients' judgements about the quality of their care.